2020
DOI: 10.1002/tqem.21687
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption of chromium (VI) from textile waste water using luffa cylindrica activated carbon

Abstract: Luffa cylindrica was applied as a low-cost adsorbent for removing chromium (VI) from textile industry effluent in this study. The adsorbent was characterized using scanning electron micrograph (SEM). A batch mode experiment was conducted to study the effect of pH, contact time, and adsorbent dosage on the adsorptive potential of the prepared luffa cylindrica activated carbon. The characterization results from SEM indicate that the adsorbents' potential was fully exploited in this study. A significance test con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 56 publications
1
5
0
1
Order By: Relevance
“…A maximum Cr (VI) removal efficiency of 97% was achieved using activated carbon derived from paper sludge [44]. It was also reported a maximum adsorption capacity of 188.5 mg/g using activated carbon derived from luffa cylindrica [45]. Moreover, many studies have been undertaken to evaluate the potential of employing water hyacinth (Eichhornia crassipes) as an adsorbent for chromium removal from wastewater [46][47][48].…”
Section: Introductionmentioning
confidence: 99%
“…A maximum Cr (VI) removal efficiency of 97% was achieved using activated carbon derived from paper sludge [44]. It was also reported a maximum adsorption capacity of 188.5 mg/g using activated carbon derived from luffa cylindrica [45]. Moreover, many studies have been undertaken to evaluate the potential of employing water hyacinth (Eichhornia crassipes) as an adsorbent for chromium removal from wastewater [46][47][48].…”
Section: Introductionmentioning
confidence: 99%
“…Exhibit revealed that by an increase in contact time, the removal efficiency of heavy metal increased until a stable plateau region appeared at 300 min, indicating an equilibrium condition (Jeyaseelan & Gupta, 2016). For Cr(VI), removal efficiency increased from 18.2% to 93.4% when the contact time was increased from 15 to 300 min, which may be due to the presence of vacant sites at the initial stage (Barot & Bangla, 2012; Nwosu‐Obieogu & Okolo, 2020). However, there is no appreciable change in efficiency with further increase in contact time due to the deposition of ions available on adsorption sites and intraparticle diffusion processes that dominate over adsorption (Amin, Alazba, & Shafiq, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Apart from this, at low pH, the adsorption decreased due to the electrostatic repulsion of the positive‐charged (H + ) ions (Barot & Bangla, 2012; Parlayici &Pehlivan, 2019). When the pH of the solution increases, the removal percentage increases owing to electrostatic attraction of the positively charged surface over OH ‐ ions (Bayuo, Pelig‐Ba, & Abukari, 2019; Nwosu‐Obieogu & Okolo, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Luffa, as a kind of resource-rich, renewable, and degradable plant fiber, has excellent physical and chemical properties due to its unique microstructures, low density, high porosity, stable chemical composition, and strong mechanical strength. Because of these characteristics, luffa has been applied for biofibers, , biosorbents, , composite materials, and biofuel cells . A naturally disordered three-dimensional (3D) structure with porous skeletons composed of good hydrophilic cellulose and microporous channels , can not only enhance the light absorbance but also ensure the effective escape of steam, offering a perfect candidate material for SDIE devices.…”
Section: Introductionmentioning
confidence: 99%